Compound Heterozygous ITGB3 Pathogenic Variants In A Patient With Glanzmann Thrombasthenia - Lenz, Antonia; Boeckelmann, Doris; Bührlen, Martina; Dengler, Kathrin; Kunz, Jürgen; Zieger, Barbara (Archives of Clinical and Medical Case Reports, 2020)
Glanzmann Thrombasthenia is a rare platelet function disorder which is characterized by decreased expression and/or dysfunction of the platelet receptor αIIbβ3 (GPIIb/IIIa). The disease is due to alterations in ITGA2B or ITGB3 the genes encoding for the receptor subunits αIIb (GPIIb) and β3 (GPIIIa) and mostly inherited autosomal recessively. We report about a one-year old girl presenting with petechiae and hematomas shortly after birth. Platelet light transmission aggregometry was impaired after stimulation with ADP, arachidonic acid and collagen. Stimulation with ristocetin reached normal values, but showed an undulating course. Flow cytometry revealed severely decreased expression of CD41 (αIIbβ3). Molecular genetic analysis of the candidate genes and family genotyping identified two compound heterozygous variants in Exon 10 of ITGB3: c.1552C>T (p.Gln518*) and c.1639T>G (p.Cys547Gly). According to the guidelines of ACMG the variants were classified as pathogenic (Class 5). The nonsense variant c.1552C>T has not been reported before.